2013
DOI: 10.1371/journal.pone.0066934
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Gut-Associated Microbiome in Inflammatory Pouch Complications Following Ileal Pouch-Anal Anastomosis

Abstract: IntroductionInflammatory complications following ileal pouch-anal anastomosis (IPAA) for ulcerative colitis (UC) are common and thought to arise through mechanisms similar to de novo onset inflammatory bowel disease. The aim of this study was to determine whether specific organisms in the tissue-associated microbiota are associated with inflammatory pouch complications.MethodsPatients having previously undergone IPAA were recruited from Mount Sinai Hospital. Clinical and demographic information were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
82
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 50 publications
(57 reference statements)
10
82
0
Order By: Relevance
“…In the present study, Blautia spp numbers were also reduced in faecal samples of patients with pouchitis 1 year after IPAA. A recent study also reported lower levels of Blautia species in patients with pouchitis compared with patients with NP 59. Collectively, these findings suggest that monitoring Blautia spp after IPAA might be useful to discriminate between inflamed pouches and NPs.…”
Section: Discussionmentioning
confidence: 68%
“…In the present study, Blautia spp numbers were also reduced in faecal samples of patients with pouchitis 1 year after IPAA. A recent study also reported lower levels of Blautia species in patients with pouchitis compared with patients with NP 59. Collectively, these findings suggest that monitoring Blautia spp after IPAA might be useful to discriminate between inflamed pouches and NPs.…”
Section: Discussionmentioning
confidence: 68%
“…As a cross-sectional diagnostic indicator for IBD, colonic microbial profiles provide only modest delineation between patients and asymptomatic controls (Dicksved et al, 2008; Frank et al, 2007; Morgan et al, 2012), ruling out a simple, universal “magic bullet” for early diagnosis, although optimistically this need not be the case in all complex inflammatory conditions. Instead, heterogeneity among CD, UC, and subtypes within them (e.g., ileal CD) suggests that carefully chosen microbial samples could, for example, be used to improve classification under high-risk conditions such as ileal pouch surgery (Tyler et al, 2013). …”
Section: Gaps Challenges and Next Stepsmentioning
confidence: 99%
“…To date, profiling of colonic microbial communities have not yielded robust results as a cross-sectional diagnostic indicator for IBD [34,36,59], although the heterogeneous nature of CD and UC raise the possibility that mindfulness of disease subtypes may help improve classification of certain groups (e.g. individuals who experience inflammatory pouch complications following ileal pouch-anal anastomosis) [60]. Treatment response prediction also remains an attractive, but relatively unexplored, potential use of microbial profiling.…”
Section: The Future Clinical Potential Of the Microbiomementioning
confidence: 99%